2021
DOI: 10.1002/pds.5186
|View full text |Cite
|
Sign up to set email alerts
|

Prescribing of menopausal hormone therapy in Germany: Current status and changes between 2004 and 2016

Abstract: Background Prescribing of menopausal hormone therapy (MHT) declined drastically after publication of the Women's Health Initiative's (WHI) findings in 2002, but studies on longer‐term trends and details of use are scarce. Methods We used the German Pharmacoepidemiological Research Database (GePaRD) containing health insurance claims data from ~25 million persons. Using data from 2004–2016, we conducted cross‐sectional analyses to determine the prevalence of MHT use overall and by type and route of administrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 30 publications
3
9
1
Order By: Relevance
“…The findings suggest an alteration in the HT user profile after 2002 with a different pattern of HT use, perhaps due to the healthiest users deciding to either drop systemic HT or switching to local HT, as recommendations changed following the WHI publication. It highlights the importance of adequate In line with previous studies, we observed a decline in systemic HT prevalence between 2000 and 2005 for systematic HT users within the menopausal or postmenopausal age [9][10][11][12] . The WHI publication in 2002, and subsequent media attention and alteration in HT prescription guidelines, is generally considered the main reason for the observed decline, as systemic HT was recommended kept in the lowest possible dosage for the shortest amount of time and was not to be used by asymptomatic women 15,23,24 .…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The findings suggest an alteration in the HT user profile after 2002 with a different pattern of HT use, perhaps due to the healthiest users deciding to either drop systemic HT or switching to local HT, as recommendations changed following the WHI publication. It highlights the importance of adequate In line with previous studies, we observed a decline in systemic HT prevalence between 2000 and 2005 for systematic HT users within the menopausal or postmenopausal age [9][10][11][12] . The WHI publication in 2002, and subsequent media attention and alteration in HT prescription guidelines, is generally considered the main reason for the observed decline, as systemic HT was recommended kept in the lowest possible dosage for the shortest amount of time and was not to be used by asymptomatic women 15,23,24 .…”
Section: Discussionsupporting
confidence: 87%
“…The association between systemic HT and all-cause mortality neither decreased nor increased the risk of all-cause mortality in initial WHI reports at both 13-years' and 18-years' follow-up [6][7][8] . The WHI publication altered the perception of systemic HT causing a drastic decrease in the prevalence of systemic HT worldwide after 2002 [9][10][11][12] .Healthy user bias has previously been hypothesised to be one of the explanations for the discrepancy in findings between observational studies and clinical trials on various outcomes, as HT users provided a better health profile at baseline 13,14 . Analysing associations before and after 2002 is especially relevant since alterations…”
mentioning
confidence: 99%
See 1 more Smart Citation
“… 5 , 13 Similar trends have been observed internationally. 14 16 The present study found a rapid increase in incident prescribing of HRT from 2015 onwards, except for the year 2020. A decrease in prescribing in 2020 may be a result of the decline in healthcare utilisation owing to restrictions imposed during the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 45%
“…Finally, we did not retain hormone replacement therapy (HRT) in our selection of bone active substances, albeit it was shown to significantly reduce hip fracture risk by approximately one-third in the Women’s Health Initiative (WHI) trials [ 34 , 35 ]. The WHI trials also showed a significant increase in breast cancers, cardiovascular diseases, and all-cause mortality which led to drastic reductions in systemic HRT use since 2002, now being mainly reserved to younger postmenopausal women with vasomotor symptoms [ 36 , 37 ]. As the effect of HRT on hip fracture risk was shown having vanished three years after discontinuation [ 38 ], we consider that omitting HRT from our analyses should not be expected to alter the present observations and conclusions.…”
Section: Discussionmentioning
confidence: 99%